The SE-Atlantic in the late pleistocene and holocene : paleoceanographic interpretations based on sedimentological, geochemical and foraminiferal data - Müllegger, Stefan (2008)
Die ozeanographische und sedimentologische Entwicklung der drei Tiefseebecken des südöstlichen Atlantiks (Kapbecken, Angolabecken, Guineabecken) während des Holozäns wurde anhand der Foraminiferenfauna und geochemisch-sedimentologischer Parameter rekonstruiert. Im Golf von Guinea spiegeln die Schwankungen der Werte des stabilen Sauerstoffs 18O in planktonischen Foraminiferenschalen ein klimagekoppeltes Heben und Senken der Thermokline (Temperatursprungschicht) wider. Sedimentologische Daten belegen deutliche Veränderungen der Tiefenwasserströme während des späten Pleistozäns und Holozäns. Das Guineabecken und das Angolabecken werden von Nordatlantischem Tiefenwasser dominiert während das Kapbecken von Antarktischem Bodenwasser durchströmt wird. Die Foraminiferenfauna zeigt einen deutlichen Trend: eine Zunahme der Diversität Richtung Äquator. The Southeast Atlantic deep-sea basins are the goal of thorough investigations concerning biodiversity as well as the oceanographic evolution during the youngest part of earth history, the Late Pleistocene and Holocene. The South Atlantic is considered to be a key region concerning ocean circulation and coupled climatic processes due to the special position in the mixing area of deep water currents from the North (North Atlantic Deep Water) and South Atlantic (Antarctic Bottom Water), both tightly connected by the Thermohaline Circulation. In the presented study we tried to link geochemical, sedimentological and faunistic data to draw a picture of the evolution of the main water currents in the region focussing on shallow water layers by the use of temperature differences stored in planktonic foraminiferal tests and on deep water by the evaluation of the effect of deep water corrosiveness fluctuations on the sediments. A second focus is on the temporal and spatial distribution patterns of benthic foraminiferal and their possible correlations to water mass and sediment properties. Due to different habitat preferences, test shapes and material as well as feeding habits ...